Genome-wide identification and expression analysis of the response regulator gene family in alfalfa (Medicago sativa L.) reveals their multifarious roles in stress response - Qiang, Yuqin; He, Xiaojuan; Li, Zhen; Li, Siqi; Zhang, Jia; Liu, Tao; Tursunniyaz, Mamateliy; Wang, Xinyu; Liu, Zhipeng; Fang, Longfa (Frontiers in Plant Science, 2023)
As important components of the two-component regulatory system, response regulatory proteins (RRPs) play a crucial role in histidine phosphorylation-mediated signal transduction in response to environmental fluctuations. Accumulating evidence has revealed that RRPs play important roles in plant growth and stress response. However, the specific functions of RR genes (RRs) in cultivated alfalfa remain ambiguous. Therefore, in this study, we identified and characterized the RR family genes in the alfalfa genome using bioinformatics methods. Our analysis revealed 37 RRs in the alfalfa genome of Zhongmu No.1 that were unevenly distributed on the chromosomes. Cis-elements analysis revealed the involvement of RRs in responses to light, stress, and various plant hormones. Expression analysis of RRs in different tissues revealed their distinct tissue expression patterns. These findings provide preliminary insights into the roles of RRs in plant responses to abiotic stress, which can be used to improve the stress tolerance of autotetraploid-cultivated alfalfa plants via genetic engineering.